Two icebergs: Difference in feminist political economy. (February 2020) - Collard, Rosemary-Claire; Dempsey, Jessica
In economic geography and beyond, a call for attention to difference or multiplicity – of logics, subjects, geographies – within capitalist and economic relations is often interpreted as a critique in the vein of JK Gibson-Graham: a call to explore capitalism's alternatives, weaknesses – 'cracks and fissures'. But there are feminist political economists for whom the multiplicity within and outside capitalism is a source of capitalism's power; capitalism functions, accumulates and reproduces itself through heterogeneity. In this commentary, we focus on a particular underused theorist who exemplifies such an approach: Maria Mies. We put Mies in conversation with the much better-known Gibson-Graham via each of their depictions of economic relations as an iceberg. We consider each iceberg (and the understanding of capitalism they represent) in relation to capitalist natures scholarship in particular, drawing on our research on the production of emaciated caribou natures in Canada as a mini 'field test' for where the icebergs direct our analytical attention. We present these icebergs as a small step towards opening up a broader terrain of feminist theorisations of capitalism and difference than is sometimes recognised in economic geography and political ecology.